Awareness and Perception of Customers on Islamic Banking Products and Services: A Meta-Synthesis - Binta Tijjani Jibril; Kabiru Tahir Hamid; Aliyu Dahiru Muhammad; Warshu Tijjani Rabi’u (Universitas Syiah Kuala, 2021)
Objective – Islamic banking has emerged as a robust and sound banking system across the globe. Despite its increasing popularity, there is a dearth of awareness in both Muslim and Non-Muslim countries which slows the pace of development of the system. This paper, there-fore, reviews critically some empirical studies on awareness and perception of Islamic bank-ing products and services.Design/methodology – The research involves review and synthesis of prior studies on customers’ awareness and perception of Islamic baking.Results – The result of the review reveals that good awareness and perception of the public on Islamic banking products and services are critical to the development of Islamic banking and finance. The study concludes that significant progress has been made in Muslim and Non-Muslim countries with the potentials to dominate conventional banking shortly in some jurisdictions.Limitation/Suggestion – Thus, the study recommends that operators and regulators of Islamic banks need to pay due attention to public awareness and perception with a view to enhancing patronage of the Islamic banking products and services and enabling the sector to effectively compete with its already well-established conventional counterpart.